An in vitro, SEM and micro-CT comparison of dentinal tubule penetration and void formation by four bioceramic sealers in premolars - Arnold, Samantha (University of Pretoria, 2024)
Dissertation (MSc (Dentistry))--University of Pretoria, 2023.